Pediatric Cytopathology A Practical Guide - Monaco, Sara E.; Teot, Lisa A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This text presents serious challenges for trainees, clinicians, and practicing pathologists and cytopathologists due to the wide spectrum of diagnoses that may be seen in children and the lack of familiarity with these entities. This reference book has been designed as a practical, high-yield review of pediatric cytopathology. Key findings are highlighted and up-to-date information is provided on the diagnosis of pediatric lesions by cytology, with extensive guidance on differential diagnosis. The book includes tables and full-color images of the cytomorphology and ancillary studies, as well as pertinent histological correlation and guidance on technical issues. Pediatric Cytopathology: A Practical Guide will be an essential reference for anyone interested in the cytomorphological findings in childhood diseases.
Introduction -- Fine Needle Aspiration in Pediatric Patients: Approach and Technique -- Lymph Nodes -- Head and Neck -- Soft Tissue and Bone -- Mediastinum and Lung -- Kidney, Adrenal, and Retroperitoneal -- Liver, Bile Ducts, and Pancreas -- Body Fluids -- CSF and CNS Cytology -- Artifacts, Contaminants and Mimics in Cytology.
Keywords: Medicine; Oncology; Pathology; Pediatrics; Medicine & Public Health; Pathology; Pediatrics; Oncology